Analisis Perpindahan Panas pada Saluran Berliku Berpenampang Segi Empat dengan Variasi Clearance Belokan - Wahyudi, Slamet; Kurniawan, Aris; Hamidi, Nurkholis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2010)
Heat transfer characteristics in rectangular with a sharp 180o turn have been examined experimentally using the naphthalene sublimation method. The sharp 180Â° turn was obtained by dividing a rectangular passage into two channels using a divider wall with a rounded tip at the location where the flow negotiates the turn. The channel cross-section (WxH) is 50Ã—25 m, and three turn clearances of 30, 50, and 70 mm have been tested in this study. Local mass transferrates on all walls of the channel have been measured to clarify the heat transfer characteristics in the channel. The result indicated that the highest coefficient of heat transfer was achieved in the channel with turn clearances of 30 mm.Keywords: Heat Transfer Characteristics in Rectangular,Turn Clearances, Mass Transfers